Ambulatory pH-impedance-pressure monitoring as a diagnostic tool for the reflux–cough syndrome. Issue 1 (27th September 2017) - Herregods, T V K; Pauwels, A; Jafari, J; Sifrim, D; Smout, A J P M; Bredenoord, A J; Tack, J
Summary: Gastroesophageal reflux is considered to be a significant contributing factor to chronic unexplained cough. Patients are often presumed to have reflux-induced cough and are exposed to high-dose and long-term empirical therapy with proton pump inhibitors (PPIs) despite the limited treatment efficacy in this population. We aimed to assess the diagnostic value of 24-hour ambulatory pH-impedance-pressure monitoring for the diagnosis of reflux-induced chronic cough. In this multicenter study, we evaluated 192 patients with chronic cough using 24-hour pH-impedance-pressure monitoring off PPIs. Manometry was used to detect all cough bursts while pH-impedance allowed for the evaluation of all reflux episodes, including weakly acidic reflux. The symptom association probability was used to determine a temporal relationship between reflux and cough. A diagnosis of reflux-induced cough was made in 25.5% of the patients. If only acid reflux episodes were used, 22.4% of those patients would not have been diagnosed. Significantly more patients with reflux-induced cough had typical reflux symptoms ( P  = 0.031) and a pathological distal acid exposure time ( P  = 0.025) in comparison to patients without the diagnosis. A diagnosis of cough-induced reflux was made in 24.0% of the patients. Only 59% of all cough bursts were registered by the patients. Overall, only approximately one quarter of patients with chronic unexplained cough have reflux-induced cough, explaining the observation that the vast majority of patients with chronic cough do not benefit from antireflux therapy. pH-impedance-pressure monitoring helps to identify patients who are likely to have reflux as a cause of their chronic cough.